The Complex Relationship Between Chronic Obstructive Pulmonary Disease With Cardiovascular Disease and Their Interactions With COVID‐19 Vaccination: A Retrospective Study - Muhammad Muneeb Hassan; Sheikh Muhammad Sikandar; Farrukh Jamal; Muhammad Ameeq; Alpha Kargbo (Immunity, Inflammation and Disease)
ABSTRACT Background Previously, most researchers explored the association between chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD). This study investigates the distinct influence of COVID‐19 vaccination status on patients with both conditions. Objective We investigate the relationship between COPD and CVD in a cohort of 838 individuals who presented with both conditions. Our aim is to understand how these conditions interact and how COVID‐19 vaccination status affects patient outcomes. Methods A retrospective analysis was conducted on 838 patients with COPD and CVD treated at DHQ Hospital in Muzaffargarh, Punjab, Pakistan, from November 2022 to April 2023. We employed multiple logistic regression and the Wilcoxon signed‐rank test to assess the odds ratio and relative risk of COPD in patients with‐CVD under various conditions. Additionally, we analyzed time‐to‐death and survival using Kaplan–Meier methods. Results Findings reveal a 7.95 times higher risk of death in patients without COVID‐19 vaccination compared with those who were vaccinated (95% CI, 6.12–10.33). Conversely, COVID‐19‐vaccinated patients exhibited a 0.221 times lower risk of recovery than their nonvaccinated counterparts (95% CI, 0.08–0.60). We also observed significant differences in time‐to‐death and recovery based on the presence of COPD and CVD, with vaccinated patients generally experiencing milder disease. Conclusion Our study assessed the impact of COVID‐19 vaccination status on patient outcomes in patients with overlapping COPD and CVD. Individuals diagnosed with COPD and CVD display significant differences in terms of their probability of survival, with those who have received vaccinations.